Distal Medium Vessel Occlusions Can Be Accurately and Rapidly Detected Using Tmax Maps. Issue 10 (October 2021) - Amukotuwa, Shalini A.; Wu, Angel; Zhou, Kevin; Page, Inna; Brotchie, Peter; Bammer, Roland
Abstract : Background and Purpose: Distal medium vessel occlusions (DMVOs) are increasingly considered for endovascular thrombectomy but are difficult to detect on computed tomography angiography (CTA). We aimed to determine whether time-to-maximum of tissue residue function ( Tmax ) maps, derived from CT perfusion, can be used as a triage screening tool to accurately and rapidly identify patients with DMVOs. Methods: Consecutive code stroke patients who underwent multimodal CT were screened retrospectively. Two experienced readers evaluated all patients' Tmax maps in consensus for presence of delay in an arterial territory (territorial Tmax delay). The diagnostic accuracy of this surrogate for identifying DMVOs was determined using receiver-operating characteristic analysis. CTA, interpreted by 2 experienced neuroradiologists with access to all imaging data, served as the reference standard. Diagnostic performance of 4 other readers with different levels of experience for identifying DMVOs on Tmax versus CTA was also assessed. These readers independently assessed patients' Tmax maps and CTAs in 2 separate timed sessions, and areas under the receiver-operating characteristic curves were compared using the DeLong algorithm. The Wilcoxon signed-rank test was used to comparatively assess diagnostic speed. Results: Three hundred seventy-three code stroke patients (median age, 70 years; 56% male, 70 with a DMVO) were included. Territorial Tmax delay had a sensitivity of 100% (CI95, 94.9%–100%) and specificity of 87.8% (CI95, 83.6%–91.3%) for presence of a DMVO, yielding an area under the receiver-operating characteristic curves of 0.939 (CI95, 0.920–0.957). All 4 readers achieved sensitivity >95% and specificity >84% for detecting DMVOs using Tmax maps, with diagnostic accuracy (area under the receiver-operating characteristic curves) and speed that were significantly ( P <0.001) higher than on CTA. Conclusions: Territorial Tmax delay had perfect sensitivity and high specificity for a DMVO. Tmax maps were accurately and rapidly interpreted by even inexperienced readers, and causes of false positives are easy to recognize and dismiss. These findings encourage the use of Tmax to identify patients with DMVOs. Abstract : Supplemental Digital Content is available in the text.